2021
DOI: 10.1111/gwao.12638
|View full text |Cite
|
Sign up to set email alerts
|

Black lives and bodywork matters: A postcolonial critique of gender and embodiment in Nigeria

Abstract: Drawing on the theories of “Womanism” and “African feminism,” this paper explores the concept of embodiment within an African context. More specifically, we focus on exploring the lived experiences of Nigerian women in male‐dominated organizations (sector) to provide an in‐depth understanding of the dynamics of how the Nigerian society marginalizes qualities and aspects of embodiment and disembodiment of women. Based on 39 interviews, our findings reveal that cultural and social practices significantly influen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 44 publications
0
1
0
Order By: Relevance
“…In this way, our work also speaks to a wider organizational literature highlighting othering (e.g., Collins, 1986) and which theorizes identity as a dynamic, contextualized process that may include flows of advantage and disadvantage in relation to intersecting positionalities (Kagher et al., 2021). For example, Atewologun, Sealy and Vinnicombe (2016, p. 223) showed that British Black and Asian women and men experience their intersecting identities in ways that can be advantageous as well as restrictive.…”
Section: Introductionmentioning
confidence: 74%
“…In this way, our work also speaks to a wider organizational literature highlighting othering (e.g., Collins, 1986) and which theorizes identity as a dynamic, contextualized process that may include flows of advantage and disadvantage in relation to intersecting positionalities (Kagher et al., 2021). For example, Atewologun, Sealy and Vinnicombe (2016, p. 223) showed that British Black and Asian women and men experience their intersecting identities in ways that can be advantageous as well as restrictive.…”
Section: Introductionmentioning
confidence: 74%